RISK LEVEL ANALYSIS OF LIGHTNING STRIKE WITH SIMPLE ADDITIVE WEIGHTING METHOD IN GOWA REGION - Priadi, Ramadhan; Hududillah, Teuku Hafid (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2018)
Gowa regency is one of the areas in the province of South Sulawesi that has a high potential of lightning events. This is influenced by its geographical location which is close to the mountainous area. This research purpose to analyze the risk level of lightning strike hazard in Gowa regency using Simple Additive Weighting (SAW) method. This research uses lightning strike data from lightning detector boltek sensor recorded by LD2000 software. The data used is event data in 2015 with sensor coordinates of 5.218° S and 119.470° E and using a density grid of 0.01o. The results for Gowa district have a total density of 26797 strikes/kilometers with clustered areas are Tinggi Moncong subdistricts and Bungaya subdistricts which each have a density value of 10443 strikes/kilometers and 5197 strikes/kilometers. The results of this study are expected to represent the level of lightning vulnerability as a reference for making adequate grounding system in areas with high lightning activity in Gowa regency.